A redescription of Stenopora and the type species Stenopora tasmaniensis Lonsdale, 1844 (Trepostomata, Bryozoa). (November 2021) - Reid, Catherine M.
Abstract: Type material for Stenopora tasmaniensis Lonsdale, 1844 was lost in the late nineteenth century, and subsequent descriptions of the genus have been based on material incorrectly assigned to the type species. A neotype is erected for S. tasmaniensis from the original type locality and the genus redescribed. The genus exhibits ramose, frondescent, encrusting, and massive colony morphologies, diaphragms are absent, and acanthostyles of a single size surround each aperture. This single size of acanthostyles aligns with the original type species description; however, it differs from the subsequently accepted genus description and may result in existing species being removed from the genus. Analysis of zooecial characters of a single colony exhibiting both frondescent and ramose morphologies reveals statistically significant differences between subsampled sections, despite being from the same colony. Differences relate to details of zooecial parameters and are not controlled by colony morphology. This variation within a single colony confirms the importance of using qualitative characters alongside quantitative measures in defining Paleozoic bryozoan species.